2020
DOI: 10.1063/5.0023000
|View full text |Cite
|
Sign up to set email alerts
|

Probing the dye–semiconductor interface in dye-sensitized NiO solar cells

Abstract: The development of p-type dye-sensitized solar cells (p-DSSCs) offers an opportunity to assemble tandem photoelectrochemical solar cells with higher efficiencies than TiO2-based photoanodes, pioneered by O’Regan and Grätzel [Nature 353, 737–740 (1991)]. This paper describes an investigation into the behavior at the interfaces in p-DSSCs, using a series of BODIPY dyes, BOD1-3. The three dyes have different structural and electronic properties, which lead to different performances in p-DSSCs. We have applied pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…668,688 The surface electronic states at the interface between NiO and a series of bodipy dyes have been studied by hard and soft XPS and the good overlap between the dye HOMO and semiconductor valence states was consistent with rapid light-induced charge transfer. 660 Recombination at the dye À /NiO + interface, however, is also fast, occurring on a picosecond to nanosecond time scale in simple dye systems such as bodipy and perylene. 660,715,716 Regeneration occurs from a nanosecond up to microsecond time scale.…”
Section: Photoelectrochemistry and Photovoltaic Performancementioning
confidence: 99%
See 2 more Smart Citations
“…668,688 The surface electronic states at the interface between NiO and a series of bodipy dyes have been studied by hard and soft XPS and the good overlap between the dye HOMO and semiconductor valence states was consistent with rapid light-induced charge transfer. 660 Recombination at the dye À /NiO + interface, however, is also fast, occurring on a picosecond to nanosecond time scale in simple dye systems such as bodipy and perylene. 660,715,716 Regeneration occurs from a nanosecond up to microsecond time scale.…”
Section: Photoelectrochemistry and Photovoltaic Performancementioning
confidence: 99%
“…660 Recombination at the dye À /NiO + interface, however, is also fast, occurring on a picosecond to nanosecond time scale in simple dye systems such as bodipy and perylene. 660,715,716 Regeneration occurs from a nanosecond up to microsecond time scale. Competition between recombination and regeneration is responsible for the poor efficiency for p-type DSCs.…”
Section: Photoelectrochemistry and Photovoltaic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…30,[52][53][54] For the last approach it has been found that the thermal treatment has the advantage of increasing the optical transparency of the NiO film, but it also brings about a significant diminution of the number of surface sites for dye-anchoring. 51,55 An efficacious way of passivating the surface of NiO is the addition of CDCA either in the electrolyte of the p-DSC, 30 or in the dyeing solution of NiO. 57 This is because CDCA reacts with the Ni(III) centres and renders them totally inactive towards recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of small and still powerful electronic devices requires a deeper understanding of physical effects especially affecting the electronic properties of solid state materials. Especially 3d metals are among the most widely used for engineering purposes [1][2][3][4][5] . The 3d metals and their alloys cover a wide range of electronic properties such as semiconductors (Cu 2 O), superconductors (cuprates) or metal to insulator transitions in e.g.…”
Section: Introductionmentioning
confidence: 99%